Vederlagsgrundande mätning med skördare - Östensson, Jesper (2014)
This study was performed in collaboration with Moelven Skog AB, Örebro district. The purpose of the study was to review existing literature in order to describe the current status of harvester based measurement technology as the way to provide information for calculating payment to the forest owners. In addition to this, a short survey was conducted to find out how a switch to harvester based measurement would affect the administrative workload on timber purchasers working for the district.